Racehorses from a breeding farm in Tropical Ecuador have a high seroprevalence of anti-Leptospira spp. antibodies: a paradigm for leptospirosis management from a One Health perspective - Orlando, Solon Alberto; Paez Martinez, Katherine; Sanchez, Ericka; de la Cruz, Carmen; Calderon, Joselyn; Arcos, Fabrizio; Torres-Lasso, Pablo; Calvopiña, Manuel; Garcia-Bereguiain, Miguel Angel (Frontiers in Tropical Diseases, 2023)
Background Leptospirosis is a zoonotic disease of worldwide distribution that affects humans and domestic and wild animals, and it is highly endemic in Ecuador. However, no reports of infections affecting horses have been published in the country. Methods This study evaluates the prevalence of anti-Leptospira spp. antibodies in racing horses from a breeding farm in the coastal Santa Elena province, southwest Ecuador. Sera were collected from 108 non-vaccinated horses and evaluated for 24 serovars of Leptospira spp. using the microscopic agglutination test (MAT). Results It was found that 100% of horses were reactive for Leptospira spp., most of them for multiple serovars. The most prevalent serovars were Leptospira kirschneri serovar Grippotyphosa (100%; 95% CI 99.9% to 100.1%); L. interrogans serovars Sejroe (96.3%; 95% CI 96.2% to 96.4%), Saxkoebing (95.4%; 95% CI 95.3% to 95.5%), Canicola (90.7%; 95% CI 90.5% to 90.9%), Icterohaemorrhagiae (80.5%; 95% CI 80.4% to 80.6%), Bataviae (73.1%; 95% CI 73.0% to 73.2%), Australis (75.0%; 95% CI 74.9% to 75.1%), and Bratislava (71.2%; 95% CI 71.1% to 71.4%); and L. borgpetersenii serovar Tarassovi (76.8%; 95% CI 76.6% to 77.0%). Conclusions We found a high prevalence of anti-Leptospira spp. seropositivity in racehorses from a breeding farm in Ecuador. This is the first serologic report for leptospirosis in horses in Ecuador. “One Health”-based sanitary practices for horse-breeding farms are recommended to improve animal and human health.